CMEs in the heliosphere: II. A statistical analysis of the kinematic properties derived from single-spacecraft geometrical modelling techniques applied to CMEs detected in the heliosphere from 2007 to 2017 by STEREO/HI-1 - Barnes,D; Davies,JA; Harrison,RA; Byrne,JP; Perry,CH; Bothmer,V; Eastwood,JP; Gallagher,PT; Kilpua,EKJ; Moestl,C; Rodriguez,L; Rouillard,AP; et al. (Solar Physics, 2019)
Recent observations with the Heliospheric Imagers (HIs) onboard the twin NASA Solar Terrestrial Relations Observatory (STEREO) spacecraft have provided unprecedented observations of a large number of coronal mass ejections (CMEs) in the inner heliosphere. In this article we discuss the generation of the HIGeoCAT CME catalogue and perform a statistical analysis of its events. The catalogue was generated as part of the EU FP7 HELCATS (Heliospheric Cataloguing, Analysis and Techniques Service) project ( www.helcats-fp7.eu/ ). It is created by generating time/elongation maps for CMEs using observations from the inner (HI-1) and outer (HI-2) cameras along a position angle close to the CME apex. Next, we apply single-spacecraft geometric-fitting techniques to determine the kinematic properties of these CMEs, including their speeds, propagation directions, and launch times. The catalogue contains a total of 1455 events (801 from STEREO-A and 654 from STEREO-B) from April 2007 to the end of August 2017. We perform a statistical analysis of the properties of CMEs in HIGeoCAT and compare the results with those from the Large Angle Spectrometric Coronagraph (LASCO) CDAW catalogues (Yashiro et al.J. Geophys. Res. Space Phys.109, A07105, 2004) and the COR-2 catalogue of Vourlidas et al. (Astrophys. J.838, 141, 2004) during the same period. We find that the distributions of both speeds and latitudes for the HIGeoCAT CMEs correlate with the sunspot number over the solar cycle. We also find that the HI-derived CME speed distributions are generally consistent with coronagraph catalogues over the solar cycle, albeit with greater absolute speeds due to the differing methods with which each is derived.